INSTALLING A SMALL-SCALE SOLAR POWER SYSTEM AS AN ALTERNATIVE ELECTRICITY SOURCE FORM RENEWABLE ENERGY AT SUKAWIJAYA VILLAGE - Hendarko Hendarko; Tri Desmana Rachmilda; Muhammad Marshal Nugroho; Rafi Rabbani Firdaus (Center for Rural Areas Empowerment (P2D), Institut Teknologi Bandung, 2024)
This paper describes a community service activity on installing a small-scale solar power system at Sukawijaya Village as an energy conversion system from solar energy to electricity that is ready to use for public. The activity began with a field survey to observe intensity of sunlight exposure as well as possible location suitable for placing the solar panels. Since the electricity network of state company is already exist in this village, it is decided to install on- grid solar panels to support the electricity usage of the community. Polycrystalline 600 Wp solar panels are installed on light steel supporting frames in open space accompanied by a 1000 W grid-tie inverter, some electrical protections, and other complementary electrical devices arranged in a panel box. PVSyst software is then used to simulate the operations of the installed solar power system. The simulation results conclude that the solar power system has performance ratio of 80% and may produce 858 kWh electricity per year. Last but not least, a workshop on the function, working principle, and maintenance of the solar power system is also conducted as a means of educating the public. The small-scale solar power system which has been installed at Sukawijaya Village would be beneficial not only as an electricity source but also as a means of educational tourism.